PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI GARUDA ELECTRIC POWER - Citra Prastika Arum Sitoresmi; M. Khoiri (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to analyze the presence or absence of the influence of discipline and work motivation on the performance of employees at PT Garuda Electric Power which is engaged in contracting. The phenomenon of employee performance levels at PT Garuda Electric Power, shows that employee performance has not been maximized. This study used two independent variables, namely the discipline variable, and the work motivation variable and used one dependent variable, namely employee performance. The data collection technique method used in this study was the distribution of questionnaires using the saturation sampling method, where the population and samples used in this study were all employees working at PT Garuda Electric Power with a population of 105 people. This research uses data analysis techniques such as validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination test, and hypothesis test. The results of this study show that disciplinary variables have a positive and significant influence on employee performance, work motivation variables have a positive and significant influence on employee performance, and also disciplinary variables and work motivation together simultaneously have a positive and significant effect on employee performance at PT Garuda Electric Power. The variables contained in this study had an influence of 45.7% on employee performance. The remaining 54.3% was influenced by other variables that came from outside this study.